2014
DOI: 10.4103/0974-9233.124082
|View full text |Cite
|
Sign up to set email alerts
|

Refractive surgery in systemic and autoimmune disease

Abstract: Patients with underlying systemic disease represent challenging treatment dilemma to the refractive surgeon. The refractive error in this patient population is accompanied by a systemic disease that may have an ocular or even a corneal component. The literature is rather sparse about the use of laser refractive surgery (LRS) and such procedure is not approved by the United States Food and Drug Administration (FDA) in this patient population. Patients with collagen vascular disease, diabetes mellitus (DM), alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…However, some authors have observed that patients with well-controlled diabetes present good refractive outcomes [ 53 , 54 ]. The risk of complications after laser refractive surgery is related to poor glycemic control and laser refractive surgery may be safe in patients with no systemic or ocular complications [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have observed that patients with well-controlled diabetes present good refractive outcomes [ 53 , 54 ]. The risk of complications after laser refractive surgery is related to poor glycemic control and laser refractive surgery may be safe in patients with no systemic or ocular complications [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, certain systemic diseases, such as autoimmune or connective tissue diseases, are still considered as contraindications for LASIK. The United States Food and Drug Administration (FDA) and the American Academy of Ophthalmology (AAO) have established lists of contraindications, but these recommendations are largely based on limited evidence [ 2 ]. The presence of systemic diseases such as rheumatoid arthritis, systemic lupus erythematosus, Sjögren’s syndrome, or inflammatory bowel disease is considered as a relative contraindication, and therefore, patients with stable and asymptomatic conditions are still frequently excluded from LASIK surgery [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…While it is not clear if this risk is compounded in patients who had keratitis or ulceration prior to LASIK, the risk of future disease warrants caution. Although LASIK is safe in patients with well-controlled autoimmune conditions [33, 34] and other immune-mediated inflammatory diseases, there have been reported cases of necrotizing keratitis post-LASIK in patients with well-controlled IBD [35].…”
mentioning
confidence: 99%